Hirschsprung’s Disease and Associated Congenital Heart Defects: A Prospective Observational Study from a Single Institution - Tuo, Giulia; Pini Prato, Alessio; Derchi, Maria; Mosconi, Manuela; Mattioli, Girolamo; Marasini, Maurizio (Frontiers in Pediatrics, 2014)
Objectives: to define the prevalence and characteristics of associated congenital heart diseases in patients with Hirschsprung’s disease. Method: all patients with a histological diagnosis of Hirschsprung’s disease admitted to our hospital between January 2010 and December 2013 were included in this prospective observational study and underwent cardiovascular screening. Cardiac anatomy was assessed by a segmental echocardiographic approach. Measurements of aortic root and left ventricular dimensions, wall thickness and function were obtained. Congenital heart diseases requiring a percutaneous or surgical intervention were described as major hearts diseases. Results: 133 consecutive patients were enrolled at median age of 2.3 years. Eleven patients (8.3%) presented an associated heart disease. Moreover five patients had mild dilatation of aortic root. 6/11 (4.5%) patients had a major congenital heart diseases requiring surgical repair. Conclusions: prevalence of associated congenital heart diseases was slightly higher than in previous papers, and mostly represented by septal defects. 4/6 patients with major heart disease had also a chromosomal anomaly. If we do not consider the subpopulation of patients with a chromosomal anomaly, cardiac defects were present in 3.8% of the patients. Based on these results we suggest to perform routine echocardiogram in all Hirschsprung patients, with or without associated chromosomal syndromes.